Membrane Biochips. (December 2002) - Fang, Ye; Frutos, Anthony G.; Webb, Brian; Hong, Yulong; Ferrie, Ann; Lai, Fang; Lahiri, Joydeep
Membrane-bound proteins represent the single most important class of drug targets. This article discusses the issues surrounding fabrication of membrane–protein microarrays by conventional robotic pin printing techniques. Ligand binding selectivity and specificity to G protein-coupled receptor (GPCR) microarrays are presented. The potential applications of these arrays for drug screening are discussed.